2017
DOI: 10.1002/etc.3869
|View full text |Cite
|
Sign up to set email alerts
|

Standardized toxicity testing may underestimate ecotoxicity: Environmentally relevant food rations increase the toxicity of silver nanoparticles to Daphnia

Abstract: Daphnia in the natural environment experience fluctuations in algal food supply, with periods when algal populations bloom and seasons when Daphnia have very little algal food. Standardized chronic toxicity tests, used for ecological risk assessment, dictate that Daphnia must be fed up to 400 times more food than they would experience in the natural environment (outside of algal blooms) for a toxicity test to be valid. This disconnect can lead to underestimating the toxicity of a contaminant. We followed the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 66 publications
4
26
0
Order By: Relevance
“…Under these ideal, constant conditions daphnids can produce hundreds of eggs, but under limiting food conditions they can slow or halt reproduction. Previous studies have shown that effects on daphnid survival, growth, and reproduction are observed at much lower toxicant concentrations when daphnids are provided with food rations that are more environmentally relevant than those used in standard toxicity tests (Coors et al 2004; Stevenson et al 2017), a finding that has broad implications for extrapolating results from toxicity tests to environmental risk assessments. The food rations used in the present study, 10 000 cells/mL/daphnid/d and 50 000 cells/mL/daphnid/d correspond to approximately 0.01 and 0.1 mg C/daphnid/d, respectively, and represent an environmentally relevant range of food concentrations likely to be encountered by daphnids in temperate lakes (McCauley and Murdoch 1987; Murdoch et al 1998; Stevenson et al 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under these ideal, constant conditions daphnids can produce hundreds of eggs, but under limiting food conditions they can slow or halt reproduction. Previous studies have shown that effects on daphnid survival, growth, and reproduction are observed at much lower toxicant concentrations when daphnids are provided with food rations that are more environmentally relevant than those used in standard toxicity tests (Coors et al 2004; Stevenson et al 2017), a finding that has broad implications for extrapolating results from toxicity tests to environmental risk assessments. The food rations used in the present study, 10 000 cells/mL/daphnid/d and 50 000 cells/mL/daphnid/d correspond to approximately 0.01 and 0.1 mg C/daphnid/d, respectively, and represent an environmentally relevant range of food concentrations likely to be encountered by daphnids in temperate lakes (McCauley and Murdoch 1987; Murdoch et al 1998; Stevenson et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Calculation of survivorship of individuals from birth to age x , l ( x ), and the fecundity schedule (average number of offspring born/d to a female of age x ), b ( x ) from the start ( x = 0) until the end of the experiment, and x = k were as outlined in Stevenson et al (2017) and are briefly described here. We calculated r from our entire data set by numerically solving the Euler equation using the uniroot function in R Statistical Software (Ver 3.6.1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of algae concentrations on the interactions between NP and algae is yet to be determined, but high algal concentrations may lead to the heteroagglomeration of algae and NP. According to Stevenson et al [29], using environmentally relevant algae concentrations in a chronic Daphnia pulicaria exposure to nano Ag significantly increased the adverse effects compared to the normal feeding rate recommended by the D. magna chronic toxicity test (OECD 211) guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…As eutrophication and algal blooms are becoming more and more common in freshwater lakes [28], the addition of algae in the test medium helps to mimic environmental conditions. On the other hand, the toxicity results obtained in the presence of algae may not be valid for the periods outside of algal blooms, when algal concentrations may be up to 400 times lower compared to those used in OECD 211 tests [29]. ISO 14371 freshwater sediment toxicity testing with ostracods requires using even more elevated algal concentrations (7.5 × 10 6 cells/mL) that exceed even the highest possible algal concentrations in nature [30,31].…”
Section: Introductionmentioning
confidence: 99%